Type-specific prevalence of Human Papillomavirus infection among women in the Northwest Territories, Canada - Y. Jiang; P. Brassard; A. Severini; V. Goleski; M. Santos; A. Leamon; S. Chatwood; C. Lys; G. Johnson; T. Wong; A. Kotaska; K. Kandola; et al. (Elsevier, 2011)
Summary: Background: Certain types of Human Papillomavirus (HPV) are highly associated with cervical cancer and precursor lesions (dysplasia), but the distribution of HPVs in Northern Canada is largely unknown. This study determined the prevalences of HPV infection due to different virus types and the association of different virus types with cervical dysplasia in the Northwest Territories (NWT). Methods: Between April 2008 and March 2009, women who underwent routine Pap testing in the NWT were included in the study. An in-house Luminex assay detected type-specific HPV infections. The HPV prevalence rates and population attributable risk fractions were calculated. Results: In 5725 bio-samples, the overall HPV prevalence was 24.2%, and of the HPV-positive samples, 76.6% harbored high-risk types, 35.2% harbored multi-type infections, and 21.6% harbored HPV16 or 18 infections. The HPV prevalence was approximately 50% higher among Aboriginal than non-Aboriginal women. The age-specific HPV prevalence exhibited a U-shape distribution in the Aboriginal group. The prevalence of HPV16 or 18 infections found in high-grade lesions was 34.1%. Among this study population, 89.5% of the cases with cervical dysplasia were attributable to HPV infection, with 27.1% attributable to HPV16/18. Conclusion: The high prevalence of high-risk HPV in this population, particularly in the Aboriginal group, will require further studies to identify specific predictors of infection. Keywords: Human Papillomavirus, Type-specific, Prevalence